Farmers on the front line: Perceptions, practices and discrepancies from the Aral Sea's Karakalpakstan and Khorezm regions - Djumaboev, Kakhramon; Amirova, I.; Primov, A.; Ishchanov, J. (Wiley, 2024)
Undesirable changes in surface water and groundwater resources and land quality for biophysical and institutional reasons will further endanger the livelihoods of people in Central Asia. The farmers' understanding of these problems and the adaptation and solution strategies they opt for are the critical variables in devising relevant policies. Our findings captured significant disparities between farmer-perceived water shortages and officially documented water availability, as well as soil salinity discrepancies. Farmers' coping strategies, including crop alterations and water-saving measures, often lead to tradeoffs, such as reduced crop yields. The study highlights the need to consider farmer perceptions and practices along with official data when designing policies. Effective policymaking must consider this dynamic interplay and the multifaceted challenges faced by farmers in these vulnerable Aral Sea regions.